Arctic Ocean sensitivity tests to doubling of riverine carbon and nutrient delivery simulated by the NEMO-PISCES model - Terhaar, Jens; Orr, James; Ethé, Christian; Regnier, Pierre; Bopp, Laurent (SEANOE, 2019)
This dataset provides model output from idealized NEMO-PISCES simulations on the ORCA1 configuration. The output includes five 80-years simulations: (1) a control run with pre-industrial CO2 concentrations (CTL), (2) a simulation with a 1% increase in atmospheric CO2 per year (CO2), (3) a simulation just like CO2 but with a 1% increase in riverine DOC delivery (DOC), (4) a simulation just like DOC but with a 1% increase in riverine CT delivery (DIC), and (5) a simulation just like DIC but with a 1% increase in riverine nutrient delivery (NUT). The provided variables are annually averaged surface pH, surface aragonite saturation state, depth-integrated CT, air-to-sea CO2 flux, and depth-integrated net primary production.